Efeitos da carbodiimida (EDC) na adesão dentinária de pinos de fibra de vidro em dentes obturados com diferentes cimentos endodônticos - Coelho, Beatriz Serrato (2018)
The objective of this study was to evaluate if the use of synthetic inhibitor EDC influences the adhesion of glass fiber posts and resin cements to radicular dentin of teeth filled with different endodontic sealers. Seventy-eight lower premolars were divided into three groups and obturated with different endodontic sealers (n = 26): Endofill (EN), AH Plus (AH) and Endosequence BC Sealer (BC). After the obturation, fiber post space was prepared, and each group was divided into two subgroups according to the protocol for post cementation (n = 13): using EDC and without the use of EDC (control). The specimens were submitted to a pull-out test, classified the mode of failure caused by the test and evaluation of the remaining material on the surface of the root canal after displacement of the post (SEM). For the comparison of the bond strength between post / cement / dentin, ANOVA and Student's t tests were used for independent samples, and a statistically significant difference was found between the Control and EDC subgroups only in the EN group. In the comparison between the groups, no difference was found when comparing the control subgroups. In the EDC subgroup, the AH group presented the best results. In the classification of failure modes, the score 1, 50% or more of cement was the most observed; with the exception of the EN group with EDC where score 2, less than 50% of cement, was the most prevalent. The great majority of the surfaces of the canals presented rests of endodontic sealres and resin cement. The EDC decreases bond strength when associated with EN cement, without changing the type of failure that occurs between resin cement and fiberglass post. Its best performance is associated with the AH Plus.